Pengaruh Brand Ambassador Dan Kemudahan Penggunaan Aplikasi Terhadap Keputusan Pembelian Secara Online Pada Marketplace Shopee (Studi Pada Mahasiswa Universitas Islam Malang Angkatan 2019) - Ani Ervin Churoida; Nur Hidayati; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research was conducted to students of the Islamic University of Malang Class of 2019. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the influence of brand ambassadors and convenience on purchasing decisions. The free variables used are brand ambassador and convenience, while the bound variables are purchasing decisions. The sample used in this study was 80 respondents who were students of the Islamic University of Malang class of 2019. The sampling technique used in this study is Non Probability Sampling, and sample determination using snowball sampling, The analysis methods used are instrument tests, multiple linear regression analysis, classical assumption tests, F tests and t tests, determination tests using the help of SPSS 22.0 computer software data processing. The results of this study show that brand ambassadors have a positive and significant effect on purchasing decisions. Product quality, price and promotion simultaneously affect purchasing decisions, while convenience variables do not have a positive and significant effect on purchasing decisions. Brand ambassadors and convenience simultaneously influence purchasing decisions. Keywords: Brand Ambassador, Ease and Purchasing Decision